1988
DOI: 10.1080/02614368800390141
|View full text |Cite
|
Sign up to set email alerts
|

Recreational betting: everyday activity and strategies

Abstract: This paper analyses aggregate betting behaviour as revealed by data embodied in the betting slips of off-course betting shop punters. A large sample (9000) slips were collected from three Birmingham shops belonging to a large multiple bookmaking company. Data from the slips were processed by computer. The discussion reveals some of the behavioural and preferential patterns of betting shop punters as a basis for evaluating a number of assumptions derived from the sociology of gambling which have escaped careful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…A typical example is provided by punter 60 who bet doubles and trebles on horses and SFs and RFs on dogs, staking similar sums in each case. While some punters kept their betting media separate in bets, others - (Filby and Harvey, 1988) to be a tiny proportion of the total and this is reflected in individual profiles.…”
Section: Core Puntersmentioning
confidence: 98%
See 2 more Smart Citations
“…A typical example is provided by punter 60 who bet doubles and trebles on horses and SFs and RFs on dogs, staking similar sums in each case. While some punters kept their betting media separate in bets, others - (Filby and Harvey, 1988) to be a tiny proportion of the total and this is reflected in individual profiles.…”
Section: Core Puntersmentioning
confidence: 98%
“…In a previous article (Filby and Harvey, 1988) we described some characteristics of the betting and staking patterns of betting-shop punters. The discussion was based on an analysis of aggregate data derived from a large number of betting transactions in three Birmingham betting shops.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Betting, in its various forms, is widely acknowledged as an important leisure pursuit (e.g., see Filby and Harvey, 1988). This may in large part relate to the fact that, as Saunders and Turner (1987) note, betting is: 'a form of risk taking that involves the material commodity of money and the emotional experience of excitement.'…”
Section: Costing Excitement In Leisure Bettingmentioning
confidence: 98%
“…A study of betting shops by Filby and Harvey (1988) indicated that over 20% of all bets in the UK were forecasts.…”
Section: The Uk Betting Marketmentioning
confidence: 99%